Reform of the Irish census of population - Oldham, C.H. (Statistical and Social Inquiry Society of Ireland, 1927)
The subject of this second Presidential Address which I have the honour of delivering to this Society was suggested by the circular letter (September 10, 1925) in which the Department of Local Government and Public Health announced that it had been authorised by the Executive Council to take a Census of the Population of the Irish Free State in April, 1926. It is fortunate and gratifying that the Government of Northern Ireland is also making arrangements to take a Census of their six counties on or about the same date. It ought, therefore, to be possible by a combination of these two Censuses to obtain most of the figures for an All-Ireland Census, which would make practicable a comparison of the 1926 figures with the figures of the eight previous Censuses since 1841.
President's address
Read before the Society on Thursday, 3rd December, 1925
Keywords: Population census 1926; Census reform; 314.15